English Language Learning Curriculum Development In Indonesia: An Intercultural Competence Perspective - Putri Zahra Melati; Wardah Hidayati; Selnistia Hidayani (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to analyze the development of the English Language Learning (ELL) curriculum in Indonesia through the lens of Intercultural Competence (IC). In the era of globalization, English functions not merely as a linguistic tool but as a bridge for intercultural communication and a means to foster global citizenship. Using a qualitative library research method, this study examines the evolution of Indonesia’s English curriculum, the integration of cultural sensitivity, and the practical challenges of implementation. The findings reveal a significant gap between global demands and current curriculum practices, which often prioritize grammatical mastery over intercultural skills. Furthermore, instructional materials frequently exhibit Western cultural bias while neglecting Indonesia's rich local heritage. This study identifies key strategies for improvement, including teacher capacity building in intercultural pedagogy, the localization of teaching materials, and a formal policy mandate to establish Intercultural Competence as a measurable learning outcome. Ultimately, integrating Intercultural Competence into the curriculum is essential for preparing Indonesian students to become effective communicators and responsible global citizens who remain rooted in their national identity